ARB Protection Against Podocyte-Induced Sclerosis is Podocyte AT1-Independent - Matsusaka, Taiji (2010)
In the present study, we tested the hypothesis that the reno-protective effect of ARB is dependent on the angiotensin II type 1 (AT1) receptor on podocytes. For this purpose, we generated podocyte-specific knockout mice for AT1 gene (Agtr1a), and crossed with NEP25, in which selective podocyte injury can be induced by immunotoxin, LMB2. Four weeks after LMB2, urinary albumin/creatinine ratio was not attenuated in Agtr1a knockout/ NEP25 (n=18), compared with that in control NEP25 mice (n=13) (8.08±2.41 in knockout vs. 4.84±0.73 in control). Both strains of mouse showed similar degrees of sclerosis (0.66±0.17 vs. 0.82±0.27 on 0 to 4 scale) and downregulation of nephrin (5.78±0.45 vs. 5.65±0.58 on 0 to 8 scale). In contrast, AT1 antagonist or an angiotensin I converting enzyme inhibitor, but not hydralazine, remarkably attenuated proteinuria and sclerosis in NEP25 mice. Moreover, continuous angiotensin II infusion induced microalbuminuria similarly in both Agtr1a knockout and wild type mice. Thus, angiotensin inhibition can protect podocytes and prevent development of glomerulosclerosis independently of podocyte AT1. Possible mechanisms include inhibitory effects on AT1 of other cells, or through mechanisms independent of AT1. Our study further demonstrates that measures that directly affect only non-podocyte cells can have beneficial effects even when sclerosis is triggered by podocyte-specific injury.